COMPARISON OF HAEMODYNAMIC CHANGES AFTER LARYNGEAL MASK AIRWAY INSERTION WITH PROPOFOL VERSUS SEVOFLURANE: Haemodynamic Changes - A Comparative Study - Zahoor, Maj Muhammad Umar; Mansoor, Rehan; buland, Khalid; Kazi, Waqas Ahmad; Ehsan ul Haq, Muhammad (Pakistan Armed Forces Medical Journal, 2010)
Objective: To compare haemodynamic changes on Laryngeal Mask Airway (LMA) insertion using tidal volume induction technique with sevoflurane at high concentration versus an intravenous induction with propofol. Study Design: Randomized Controlled Trial (RCT). Place and Duration of study: The study was carried out at Department of Anaesthesiology, Intensive Care and Pain Management, Military Hospital Rawalpindi from May 2006 to April 2007. Patients and Methods: One hundred patients were enrolled after written informed consent. Patients were divided in two groups. Group A received propofol and group B received sevoflurane for induction of general anaesthesia. Heart rate and mean arterial pressure (MAP) were recorded one minute before induction of anaesthesia and three minutes after induction and LMA placement. Independent sample “t-test” was applied to compare means for MAP and mean heart rate in both the groups and p value was inferred to judge the significance. Results: In group A 20 males and 30 females were enrolled for the study while in group B there were 16 males and 34 females. The mean age of the patients in group A was 30.5 ± 4.8 years while in group B was 28.4 ± 5.2 years. Mean weight was 60.5 ± 5.8 and 62.2 ± 4.7 kilograms respectively in both groups. Twenty two patients were ASA I and 28 were classified as ASA II in group A while 27 were ASA I and 23 were ASA II in group B. In the group A, MAP was recorded to be 90 ± 5.3 mmHg before induction and 79.9 ± 7.5 mmHg after LMA placement following propofol induction. Whereas MAP in Group B before induction of anaesthesia and after LMA placement were 90 ± 4.8 and 84.2 ± 7.03 mmHg respectively. The fall in MAP was found to be significant in Group A when compared to Group B after induction and insertion of LMA (p value < .005). In group A, mean HR was recorded to be 79.1 ± 4.3 before induction and 82.2 ± 8 per minute after LMA placement following propofol induction. While mean HR in Group B was 78.1 ± 7.8 before induction and 83.3 ± 8.0 per minute after LMA placement following sevoflurane induction. Hence, we found no significant difference in terms of change in mean HR between the two groups (p value > 0.4) before and after LMA insertion. Conclusion: Considering more fall in the MAP following propofol induction in group A and as there was no significant change in MAP and heart rate before and after sevoflurane induction, we conclude that sevoflurane provided better haemodynamic stability than propofol for LMA insertion.